Interobserver agreement of EUS elastography in the evaluation of solid pancreatic lesions - Soares, João-Bruno (Endosc Ultrasound, 2015)
BACKGROUND AND OBJECTIVES: Previous reports assessing the reproducibility of endoscopic ultrasound elastography (EUS-E) in evaluation of solid pancreatic lesions (SPL) involved only experienced endosonographers. We aimed to assess the interobserver agreement (IOA) of EUS-E in the evaluation of SPL by endoscopists with different levels of experience in EUS and EUS-E. MATERIALS AND METHODS: A cross-sectional observational multicenter study was designed and included 11 endoscopists who were divided into four groups: Group A (long experience in EUS and EUS-E); Group B (short experience in EUS and EUS-E); Group C (long experience in EUS and no experience in EUS-E); and Group D (no experience in EUS or EUS-E). The observers independently classified the patterns of 60 video sequences of EUS-E, after a 20-min training session. For each group, we calculated IOA (kappa statistic, κ) of EUS-E and the diagnostic accuracy of EUS-E for pancreatic malignancy, by comparing the pattern of EUS-E indicative of malignancy (heterogeneous or homogenous blue) with the final diagnosis. RESULTS: The overall IOA was moderate (κ = 0.42; 95% confidence interval (CI) 0.33-0.52). The IOA of Group A (κ = 0.80; 95% CI 0.65-1.00) was significantly higher than that of Groups B (κ = 0.54; 95%CI 0.40-0.71), C (κ = 0.54; 95%CI 0.39-0.68), and D (κ = 0.28; 95%CI 0.14-0.40). IOA of Groups B and C was not significantly different, but it was significantly higher than that of Group D. The diagnostic accuracy of Group A (area under the curve under summary receiver operating characteristic (AUROC) = 0.83; 95%CI 0.75-0.90) was not significantly different from that of Group B (AUROC = 0.77; 95%CI 0.71-0.83), but it was significantly higher than that of Groups C (AUROC = 0.74; 95%CI 0.67-0.81) and D (AUROC = 0.74; 95%CI 0.67-0.81). No significant difference was seen between Groups B, C, and D for diagnostic accuracy. CONCLUSION: EUS-E is reproducible in the evaluation of SPL, even between endoscopists with no or limited experience in EUS and/or EUS-E. Reproducibility and diagnostic accuracy increase with experience in EUS and EUS-E.